The Impact of the Relation Between Movement Patterns and Nodes Distribution on the Performance of Smart Cities - Wadullah, Wael (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In smart cities, it is believed that there exists an impact of the relation between the movement patterns of mobile nodes from one side, and their distribution from the other side, on the overall performance of the smart city. This work tries to investigate this kind of relation using simulations. To this end, experiments were designed using a variety of parameters. Different distributions were used as well as a mobility model with a routing protocol. Four kinds of experiments were designed, each of which includes different settings. The simulations were carried out and the results were obtained and then analyzed. The performance and the stability of these experiments were investigated. The results showed interesting facts about the simulations. The results of this research can be of benefit to smart city researchers. It will also be of interest when it comes to developing optimal strategies for spreading advertising in a smart environment.